Pengaruh Financial Stress dan Financial Self-Efficecy Terhadap Work Life Balance pada Karyawan Muda yang Tinggal di Rancaekek - Putri Ayu Nandini; Nur Hayati (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of financial stress and financial self-efficacy on work-life balance amoung young employees in Rancaekek Subdistrict. This study uses a quantitative approach with a descriptive correlational technique, involving 120 respondents aged between 18 and 25 who reside in Rancaekek District. Data was collected by distributing questionnaires directly, and data analysis was done using multiple linear regression through SPSS version 25, followed by processing with a non-parametric test called Spearman,s Rho. The research result show that financial stress has a negative and significant effect on work-life balance (t-count =-2,362; p = 0,020; < Sig 0,05), while financial self-efficacy has positive and significant effect on work-life balance (t-count = 9,889; p = 0,000; Sig < 0,05). At the same time, both variables have a significant effect on work-life balance. The findings indicate that as financial stress increases, work-life balance decreases, whereas as financial self-efficacy increases, work-life balance improves.